Action against Traffic Violations during the Pilkada Campaign Period by Traffic Officers in the Context of Realizing Traffic Security and Traffic Security in the Jurisdiction of the Surakarta Police - Johannes, Stevano Leonard; Nita, Surya; Gani, Yopik (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2024)
This research was motivated by the high number of traffic violations committed by participants in the 2015 Pilkada campaign. These traffic problems occurred due to low traffic awareness among the people of Surakarta. Considering the high number of traffic violations by students, the Surakartal Police Traffic Unit should prioritize taking action against violations against participants in the 2015 regional election campaign. This research was carried out to obtain an overview of the process of taking action against students by taking action against violations by the Surakartal Police Traffic Unit officers. This description includes the causes of traffic violations committed by campaign participants then with the available concepts and theories including law enforcement theory, routine activity theory and Law number 22 of 2009 concerning Road Traffic and Transportation to find out the picture of action against traffic violations. Carried out and taking into account the factors that influence the prosecution of traffic violations carried out by traffic officers within the jurisdiction of the Surakarta Police in order to create an increase in road traffic security.